Desain Manufaktur Bracket Aluminium - Raharjo, Rudianto; Widodo, Teguh Dwi; Bintarto, Redi (Jurnal Rekayasa Mesin, 2018)
Machining is one of the processes in a manufacturing of a product. Manufacturing design is needed for improving the quality of a product. The desired manufacturing process is the achievement of a product with a smooth level of roughness and a short time. Bracket is one component of a series of machines. Work on bracket using CNC milling and Turning machine. The material used is aluminum alloy 6063. The main variables in this machining process are the speed of feeding, cutting speed and feeding motion. The results achieved in the machining process of this bracket are for the roughness on the surface of the N5 with Ra (ideal) = 0.4 Î¼m of Ra (actual) = 0.410 Î¼m. As for the roughness of N6 with Ra (ideal) = 0,8 Î¼m obtained result Ra (actual) = 0,832 Î¼m and 0,625 Î¼m. Total machining time for one workpiece are 1 hour 57 minutes 25 seconds.